Literasi Financial Technology sebagai Program Pemberdayaan Masyarakat dalam Menghadapi Tantangan Industri Kreatif melalui Bumdes Mitra Lestari di Desa Bumi Sari – Kecamatan Natar, Lampung Selatan - Mahatma Kufepaksi; Hidayah Wiweko (Jurnal Pemberdayaan Umat, 2023)
Purpose: This activity aims to provide knowledge and insight to the people of Bumi Sari Village, Natar District, Lampung Selatan, especially for those who work as staff at BUMDes Mitra Lestari related to financial technology literacy. Methodology: The method used in this activity is the delivery of material in the form of coaching, discussion, and monitoring. Results: The results of this activity received positive responses from the training participants and were also able to increase participants' knowledge and insight related to financial technology. Conclusions: Based on the results of the study in general, there was an increase in the participants' post-test scores when compared to the pre-test, with a better distribution of scores. Thus, this training can be said to be successful because the participants are able to absorb the material well. Limitations: This activity has limited time for service, because in order to achieve the desired goals optimally, it is necessary to carry out activities at another time as a continuation of these activities. Contribution: Activities regarding technology-based finance are important to be disseminated to the wider community in order to face the development of the creative industry.